Mental Health of Young Couples Referred to Premarriage Consulting Center of Kashan - Zahra Sepehrmanesh; Alireza Moravveji (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Marriage is base of family creation and human race reproduction. Evaluation mental health of couples; diagnosis and treatment of mental disorder are essential and should be considered before marriage. The aim of this study was to investigate the mental health in young couple referred to consulting center before marriage. Materials and Methods: This cross-sectional study was carried out on 194 young couples. The data collection instruments included the Goldberg's General Health Questionnaire (which has 4 subunits depression, anxiety, somatic symptoms and function) and a questionnaire form consist of personal information and factors associated with mental health. Data were analyzed using, Chi-Square or Fisher exact test and t- tests. Results: The mean (SD) total GHQ score was 22.3 (8.8) in females and 18.7 (8.5) in men (P=0.004). 29.9 % men and 37% women had mental health problem. The mean (SD) total GHQ score was 21.9 (9.1) in the age group 21 to 25 which was higher than the other age groups, and in those with a higher diploma degree was 23.3 (11.7) which was higher than the other educational groups (P= 0.005). Conclusion: Young couples with age 21-25 years old, females and couples with high educational levels had lower mental health than other groups. Therefore, early screening and diagnosis of these problems can prevent impact of these disorders on job performance and social and interpersonal relationship.